Entomological assessment of tsetse-borne trypanosome risk in the Shimba Hills human-wildlife-livestock interface, Kenya - Ebhodaghe, Faith I.; Bastos, Armanda D. S.; Okal, Michael N.; Masiga, Daniel K. (Frontiers in Veterinary Science, 2022)
Shimba Hills is a wildlife area in Kenya and a major focus of tsetse-borne trypanosomes in East Africa. In Shimba Hills, tsetse-borne trypanosomes constrain animal health and smallholder livelihoods. However, epidemiological data to guide hotspot-targeted control of infections are limited. This study assessed the dynamics of tsetse-borne trypanosome risk in Shimba Hills with the objective to describe infection hotspots for targeted control. Tsetse flies (n = 696) collected in field surveys between November 2018 and September 2019 in Shimba Hills were characterised for chronological age and phenotypic sizes and screened for trypanosome and cattle DNA. Entomological inoculation rates for trypanosome risk assessment were derived from the product of fly abundance and molecular rates of vector infection and confirmed cattle bloodmeals in tsetse flies. In addition, cattle health indicators including anemia scores were assessed in contemporaneous parasitological surveys that screened livestock blood samples (n = 1,417) for trypanosome using the buffy-coat technique. Compared with Glossina brevipalpis and G. austeni, G. pallidipes was the most abundant tsetse fly species in Shimba Hills and had a wider spatial distribution and greater likelihood for infectious bites on cattle. The risk of cattle infection was similar along the Shimba Hills human-wildlife-livestock interface but high within one thousand metres from the wildlife reserve boundary. Trypanosomes in tsetse flies were highly diverse and included parasites of wild-suids probably acquired from warthogs in Shimba Hills. Age and phenotypic sizes were similar between tsetse fly populations and did not affect the probability of infection or cattle bloodmeals in the vectors. Anemia was more likely in trypanosome-positive cattle whilst parasitological infection rates in cattle samples maintained a weak relationship with entomological inoculation rates probably because of the limited time scale of sample collection. Trypanosome risk in Shimba Hills is high in locations close to the wildlife reserve and driven by G. pallidipes infectious bites on cattle. Therefore, trypanosome vector control programmes in the area should be designed to reduce G. pallidipes abundance and tailored to target sites close to the wildlife reserve.